LEXICAL SYSTEM AND COMPOSITION OF THE LANGUAGE (Academicia Globe: Inderscience Research, 2024)
This article discusses the lexical system and composition of the language. Lexicology is said to be the study of all aspects of a word, including its formation, spelling, origin, usage, and definition. Lexicology also deals with the relationships that exist between words. In linguistics, it is expressed through examples and examples that the lexicon of the language consists of lexemes, which are abstract units of meaning corresponding to the set of similar forms of the word. It has been suggested that the root is the final component that remains after removing all functional and derivational affixes and does not allow further analysis.